Human Adipose-Derived Stem Cells Accelerate the Restoration of Tensile Strength of Tendon and Alleviate the Progression of Rotator Cuff Injury in a Rat Model. Issue 3 (March 2015) - Chen, Hsin-Shui; Su, Yu-Ting; Chan, Tzu-Min; Su, Yu-Jie; Syu, Wan-Sin; Harn, Horng-Jyh; Lin, Shinn-Zong; Chiu, Shao-Chih
Adult stem cell therapy for the treatment of tendon injuries is a growing area of research. This study is aimed to investigate the efficacy of human adipose-derived stem cell (hADSC) injection on the tendon during its healing process in a rat model of rotator cuff injury. hADSCs were injected 3 days after collagenase-induced rotator cuff injuries in experimental groups, while the control group received saline as a placebo. Histological and biomechanical analyses were performed 7, 14, 21, and 28 days after collagenase injection. Compared to the control group, it was found that inflammatory cells were significantly decreased in the hADSC-treated group after collagenase injection for 7 and 14 days. In the hADSC-injected group, the fiber arrangement and tendon organization had also been improved. On the seventh day after collagenase injection, the load to failure of the hADSC-injected group (15.87 ± 2.20 N) was notably higher than that of the saline-injected group (11.20 ± 1.35 N). It is suggested that the tensile strength of the supraspinatus tendon was significantly enhanced. Local administration of hADSCs might have the possibility to restore the tensile strength and attenuate the progression of tendinitis. Taken together, these findings demonstrate that the recovery processes in damaged tendons can be facilitated architecturally and functionally after hADSC injection.